The Effect of Quartet Nusantara Media on Learning Outcomes of Social Studies on the Diversity of Indonesian Ethnic Groups and Cultures - Mahara Arigayo; Cici Cahyati; Neneng Sulastri (JURNAL PENDIDIKAN IPS, 2023)
Social Sciences is a subject that studies social life by integrating various fields of social sciences and humanities. However, students often face difficulties in understanding the concepts taught due to less engaging and interactive teaching methods and learning media. This research aims to examine the effectiveness of using Game-Based Learning (GBL) in enhancing students' proficiency in Social Sciences at MI Matlaul Huda Bandung. The research method employed is Pre-Experiment with a One Group pretest-posttest design. The research subjects are fifth-grade students at Madrasah Ibtidaiyah in Bandung Regency, Indonesia. The experimental group is provided with the treatment using the Game-Based Learning Model, specifically the Nusantara Quartet Card Game. The sample consists of 20 students from MI Matlaul Huda in Bandung Regency, and the data is analyzed using descriptive statistics. Based on the results of inferential statistical analysis using the paired t-test formula, the success rate achieved by the students is that all students obtain scores above 70. Since t-value > t-table at a significance level of 0.05, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the model has an impact on students' learning outcomes.